Colonizing multidrug-resistant bacteria and the longitudinal evolution of the intestinal microbiome after liver transplantation - Medini K. Annavajhala (Nature Portfolio, 2019)
In a large prospective cohort of liver transplantation (LT) recipients, the authors identify associations between colonization by multidrug-resistant bacteria (MDRB) and microbiome dysbiosis pre- and post-LT, suggesting colonizing MDRB as an important target for microbiome-informed therapeutic approaches post-LT.